The development and validation of micro‐CT of large deep frozen specimens. Issue 1 (30th December 2014) - Kampschulte, Marian; Erdmann, Georg; Sender, Jonas; Martels, Gunhild; Böcker, Wolfgang; ElKhassawna, Thaqif; Heiß, Christian; Langheinrich, Alexanders Claus; Roeb, Elke; Roderfeld, Martin; Krombach, Gabriele Anja
Summary Repetitive freeze/thaw cycles lead to a progressive loss of structural and molecular integrity in deep frozen specimens. The aim of this study was to evaluate a micro‐CT stage, which maintains the cryoconservation of large specimens throughout micro‐CT imaging. Deep frozen ovine vertebral segments (−20 °C) were fixed in a micro‐CT stage made of expanded polystyrene and cooled with dry ice (0 g, 60 g and 120 g). The temperature inside the stage was measured half‐hourly over a time span of three hours with subsequent measurement of surface temperature. The method was validated in a series of 30 deep frozen vertebral specimens and in liver tissue after repetitive micro‐CT scanning. Isolation without cooling resulted in defrosting. Cooling with 60 g of dry ice led to a temperature rise inside the stage (max. 5.1 °C) and on the specimen surfaces (max. −3 °C). Cooling with 120 g of dry ice resulted in a significant (p < 0.001) and sufficient lowering of the temperature inside the stage (max. −14 °C) and on the surface of the specimens (max. −13.9 °C). The surface temperature during the subsequent micro‐CT validation study did not exceed −16 °C (processing time 1 h 45 min). The resolution was 33 μm isotropic voxel side length, enabling a binarization of bone microstructures. Temperature can reliably be maintained below −10 °C during a micro‐CT scan by applying the described technique. The resulting spatial resolution and image quality permits a binarization of bone microstructure. SCANNING 37:63–72, 2015. © 2014 Wiley Periodicals, Inc.